Students' Ability to Understand Statistics Subjects: An Analytical Review - MZ, Zainudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to assess the comprehension skills of students in the statistics course at the Management Study Program, Universitas Islam Kadiri, Kediri. A survey method was employed to gather diverse information from 30 students in Semester III class A5 enrolled in the statistics course during the academic year 2022/2023. The research was conducted from July to November 2023, utilizing purposive sampling. Data collection involved a test comprising 10 multiple-choice questions, focusing on stages such as reading comprehension, understanding, transformation, process skills, and selecting the correct answers. Qualitative descriptive analysis was applied during and after data collection. The research findings indicate that students' comprehension skills in the statistics course fall into the high category, with 62% of students answering correctly. Common errors occurred in stages such as reading comprehension, understanding, transformation, process skills, and answer selection. Suggestions are given to students to study more diligently, actively participate in learning activities, and overcome difficulties by finding ways to make statistics materials more comprehensible. The Management Study Program is advised to pay special attention to challenging statistics topics to optimize students' learning outcomes.